2013
DOI: 10.1007/s12602-013-9133-3
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene Biosynthesis in Probiotic Bacteria

Abstract: Susceptibility to deadly diarrheal diseases is partly due to widespread pediatric vitamin A deficiency. To increase vitamin A coverage in malnourished children, we propose to engineer a probiotic bacterium that will produce β-carotene in the intestine, which will be metabolized to vitamin A. Such a therapy has the potential to broadly stimulate mucosal immunity and simultaneously reduce the incidence and duration of diarrheal disease. To that end, a β-carotene-producing variant of the probiotic Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Jennifer et al generated a β-carotene-producing variant of the probiotic Escherichia coli strain Nissle 1917, which had the ability to activate murine DCs in vitro . But, it is a pity that no in vivo experiments were performed to examine its immune functions (32). Compared with Nissle 1917, B. subtilis has many advantages, such as resistance to different environmental stresses, easily prepared and maintained, low storage costs.…”
Section: Discussionmentioning
confidence: 99%
“…Jennifer et al generated a β-carotene-producing variant of the probiotic Escherichia coli strain Nissle 1917, which had the ability to activate murine DCs in vitro . But, it is a pity that no in vivo experiments were performed to examine its immune functions (32). Compared with Nissle 1917, B. subtilis has many advantages, such as resistance to different environmental stresses, easily prepared and maintained, low storage costs.…”
Section: Discussionmentioning
confidence: 99%
“…The luxCDABE box makes ECN self fluorescent Balb/c mice of liver tumors Plasmid and chromosome Non invasive detection of liver cancer [ 80 ] ECNL4 Hypoxia induction 3HB promotes the growth of probiotics, improves intestinal microenvironment and alleviates enteritis DSS-induced colitis in mice Chromosome Treatment of colitis [ 81 ] ECN-BCD-BUT / Carrying BCD and BUT genes at the same time can promote the production of butyric acid in ECN. This short chain fatty acid (SCFA) can prevent and improve colitis DSS-induced colitis in mice Chromosome Treatment of colitis [ 82 ] SYNB1020 Hypoxia induction The Arginine repressor is deleted, and the N -acetylglutamate synthetase ArgA is inserted into the genome to convert NH3 into l -arginine ( l -arg) to reduce blood ammonia Mice [C57BL/6] Chromosome Treatment of hyperammonemia [ 83 ] pSB-AN IPTG induction Ethanol dehydrogenase 2 gene, aldehyde dehydrogenase 2 gene, NAD synthase gene and NADH oxidase gene promote the degradation of ethanol and acetaldehyde in the liver Alcohol fed mice Plasmid Reversing liver and intestinal injury induced by alcoholism [ 84 ] pSTBlue-BETAipi / Generated in the intestine β- Carotene can restore functional mucosal immunity and treat diarrhea caused by vitamin A deficiency / Plasmid Treatment of diarrhea caused by vitamin A deficiency [ 85 ] ΔECN((pET28a-pHLIP)) IPTG induction Knock out minCD gene and enhance minE to produce External vesicle for DOX targeted delivery 4T1 breast cancer mouse model Plasmid and Chromosome Cancer treatment [ 86 ] ECN Z/F @Au NIR light induction Gene E expression producing bacteria ghost is used for the spatiotemporal release of 5-FU and ZOL Tumor bearing mice Plasmid Cancer treatment ...…”
Section: Diagnosis and Treatment Of Various Diseases Using Geneticall...mentioning
confidence: 99%
“…Experimental results showed that the weight of β-carotene was about 0.6 ​μg/mg of dry bacteria. In vitro experiment showed that in the presence of micromolar levels of β-carotene, ECN-BETA retained its ability to stimulate dendritic cells in mice without causing immunosuppression, which preserved the beneficial immunostimulatory properties of probiotics [ 85 ].…”
Section: Diagnosis and Treatment Of Various Diseases Using Geneticall...mentioning
confidence: 99%
“…The unicellular green microalga Dunaliella salina (Chlorophyta) is rich in β-carotene, which accumulates at approximately 5-10 mg/L dry weight under suitable growth conditions, similar to other higher plants, fungi, and bacteria (Ku et al 2019;Miller et al 2013;Yen et al 2019). However, D. salina produces a large amount of β-carotene, up to 10% cellular dry weight, under abiotic-stress conditions such as high light (HL), nitrogen depletion (ND), high salt (HS), and low temperature (Abomohra et al 2019;Abomohra et al 2020;Mai et al 2017;Nguyen et al 2016;Zarandi-Miandoab et al 2019).…”
Section: Introductionmentioning
confidence: 99%